Optical film, its manufacturing method and use

JP7639334B2Active Publication Date: 2025-03-05ZEON CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020218520
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-28
Publication Date
2025-03-05
Estimated Expiration
2040-12-28

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、三次元位相差フィルムとして良好な効果を発現することができ、且つ搬送及び保存が容易であり、容易に製造することができるフィルム、及び、三次元位相差フィルムとして良好な効果を発現しうるフィルムを容易に製造することができる製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639334000001
    Figure 0007639334000001
Patent Text Reader

Abstract

To provide a film that can express good effects as a three-dimensional retardation film, and is easy to transport and store and also easy to produce, and provide a method for producing the same.SOLUTION: A long-length optical film includes a film A composed of crystalline resin (a) and a protective film B provided on one surface of it. Thickness DA of the film A and thickness DB of the protective film B satisfy DB / DA>2. The film A has an NZ coefficient of less than 1. A production method includes steps of: preparing a film pA composed of crystalline resin (a); sticking the protective film B onto one surface of the film pA; and bringing a solvent into contact with the other surface of the film pA, in the stated order.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical film, a method for manufacturing the same, and uses thereof.

Background Art

[0002] Conventionally, resin films having specific optical properties have been used for optical applications. For example, a film satisfying 0 < NZ < 1 for the NZ coefficient is called a three-dimensional retardation film. It is known that when a three-dimensional retardation film is provided in a display device such as a liquid crystal display device, it can exhibit an effect such as reducing the coloring of the display surface viewed from an inclined direction.

[0003] The three-dimensional retardation film has a larger retardation in the z-axis direction (i.e., the thickness direction) than the retardation in the y-axis direction (i.e., the in-plane direction orthogonal to the in-plane slow axis direction). Therefore, it cannot be manufactured by a normal method for manufacturing a retardation film, such as simply stretching a resin for an optical film having a normal positive intrinsic birefringence. Therefore, it has been proposed to manufacture a three-dimensional retardation film or a film similar thereto by combining a resin having a positive intrinsic birefringence and a resin having a negative intrinsic birefringence (for example, Patent Documents 1 and 2).

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Patent Document 2

Summary of the Invention

Problems to be Solved by the Invention

[0005] The manufacturing method of a three-dimensional retardation film that combines a resin with positive and a resin with negative intrinsic birefringence that has been proposed so far has problems such as requiring a complicated stretching process, requiring a lamination process after stretching, and requiring a lot of work for positioning. In particular, it is difficult to easily manufacture a film with reverse wavelength dispersion. In addition, in such a combination, it is required to increase the ratio of the resin with negative intrinsic birefringence to a certain extent or more, but since many resins with negative intrinsic birefringence generally have low mechanical strength, a problem of low mechanical strength may occur when the ratio of such a resin is increased. In addition, when the film is manufactured as a long film, if the manufacturing process includes a process of stretching in the width direction, there is a significant problem that curling of the end of the film in the width direction during transport of the long film occurs easily. In addition, when such a long film is made into a film roll, there is also a problem that the roll is easily deformed in the winding shape, and the film is easily deteriorated during storage of the film roll.

[0006] Therefore, an object of the present invention is to provide a film that can exhibit good effects as a three-dimensional retardation film, is easy to transport and store, and can be easily produced, and a manufacturing method that can easily produce a film that can exhibit good effects as a three-dimensional retardation film. [Means for solving the problem]

[0007] The present inventors have conducted studies to solve the above problems, and as a result, have found that the above problems can be solved by combining a film that uses a specific material and exhibits desired optical properties with a specific protective film, and have thus completed the present invention. That is, the present invention includes the following.

[0008] [1] A long optical film comprising a film A made of a crystalline resin (a) and a protective film B provided on one surface of the film A, a thickness DA of the film A and a thickness DB of the protective film B satisfy DB / DA>2; The optical film, wherein the NZ coefficient of the film A is less than 1. [2] The optical film according to [1], wherein the crystalline resin (a) has a positive intrinsic birefringence value. [3] The optical film according to [1] or [2], wherein the crystalline resin (a) contains an alicyclic structure-containing polymer. [4] The protective film B is made of material (b), The optical film according to any one of [1] to [3], wherein a glass transition temperature Tg(a) (°C) of the crystalline resin (a) and a glass transition temperature Tg(b) (°C) of the material (b) satisfy Tg(b)≧Tg(a)+35. [5] A method for producing the optical film according to any one of [1] to [4], A step (I) of preparing a film pA made of a crystalline resin (a); A step (II) of laminating a protective film B onto one surface of the film pA; and (III) a step of contacting the other surface of the film pA with a solvent to change the birefringence in the thickness direction of the film pA to form film A. [6] The method for producing an optical film according to [5], further comprising, after the step (III), a step (IV) of co-stretching the film A and the protective film B. [7] A step of producing the optical film by the production method according to [5] or [6]; and A method for producing a retardation film, comprising: a step (V) of peeling off the protective film B from the optical film. Effect of the Invention

[0009] According to the present invention, it is possible to provide a film that can exhibit good effects as a three-dimensional retardation film, is easy to transport and store, and can be easily produced, and a production method that can easily produce a film that can exhibit good effects as a three-dimensional retardation film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.

[0011] In the following description, the in-plane retardation Re of a layered structure (such as a film and a layer constituting a part of a film consisting of multiple layers) is a value expressed by Re = (nx - ny) x d unless otherwise specified. The retardation Rth in the thickness direction of a layered structure is a value expressed by Rth = [{(nx + ny) / 2} - nz] x d unless otherwise specified. The NZ coefficient of a layered structure is a value expressed by (nx - nz) / (nx - ny) unless otherwise specified.

[0012] nx represents the refractive index in a direction perpendicular to the thickness direction of the layered structure (in-plane direction) and giving the maximum refractive index. ny represents the refractive index in the in-plane direction of the layered structure and perpendicular to the direction of nx. nz represents the refractive index in the thickness direction of the layered structure. d represents the thickness of the layered structure. The measurement wavelength is 590 nm unless otherwise specified.

[0013] In the following description, unless otherwise specified, a material with positive intrinsic birefringence means a material whose refractive index in the stretching direction is greater than that in the direction perpendicular thereto. Also, a material with negative intrinsic birefringence means a material whose refractive index in the stretching direction is smaller than that in the direction perpendicular thereto. The value of intrinsic birefringence can be calculated from the dielectric constant distribution.

[0014] In the following description, a "long" film refers to a film having a length of 5 times or more, preferably 10 times or more, the width, specifically a film having a length that can be wound into a roll for storage or transportation. There is no particular upper limit on the length, but it is usually 100,000 times or less the width.

[0015] In the following description, unless otherwise specified, the slow axis of the layered structure is the in-plane slow axis.

[0016] 〔Optical Film〕 The optical film of the present invention is a long optical film comprising a film A made of a crystalline resin (a) and a protective film B provided on one surface thereof.

[0017] The film A has an NZ coefficient of less than 1. Specifically, the NZ coefficient NZ(A) of the film A may satisfy 0 < NZ(A) < 1 or NZ(A) < 0. The former can be usefully used as a so-called three-dimensional retardation film. The latter can be usefully used as a material for manufacturing a three-dimensional retardation film. That is, it can be easily converted into a film satisfying 0 < NZ(A) < 1 by a simple process such as uniaxial stretching.

[0018] When the film A satisfies 0 < NZ(A) < 1, NZ(A) is greater than 0, preferably 0.2 or more, while less than 1, preferably 0.8 or less. When the NZ(A) is within this range, when the optical film is provided in a display device such as a liquid crystal display device, effects such as reducing the coloring of the display surface viewed from the tilt direction can be particularly well exhibited. On the other hand, when the film A satisfies NZ(A) < 0, NZ(A) is preferably 0.7 or less, more preferably 0.6 or less. The lower limit of NZ(A) is not particularly limited, but may be 0.3 or more.

[0019] In the optical film of the present invention, the thickness DA of film A and the thickness DB of protective film B satisfy DB / DA>2. Specifically, the thickness ratio DB / DA is greater than 2, preferably 2.1 or more, more preferably 2.2 or more. The upper limit of the thickness ratio DB / DA is not particularly limited, but may be 5 or less. In general, optical films used in devices such as display devices require a certain degree of thickness to exhibit optical properties, while being thin is required due to the demand for thinner devices. By satisfying the requirements of the present invention, the optical film of the present invention can be a film in which film A satisfies the desired optical properties even if it is thin.

[0020] The thickness of film A can be appropriately adjusted to a thickness that provides desired optical properties. The thickness of film A is preferably 10 μm or more, more preferably 20 μm or more, and preferably 200 μm or less, more preferably 100 μm or less. The thickness of protective film B can be appropriately adjusted to a thickness that satisfies the above-mentioned requirements and can suitably exhibit the function of a protective film. The thickness of protective film B is preferably 50 μm or more, more preferably 100 μm or more, and preferably 500 μm or less, more preferably 300 μm or less.

[0021] The optical film of the present invention may have two or more layers of film A and may have two or more layers of protective film B, but in a preferred embodiment, it has only one layer of film A and only one layer of protective film. When it has two or more layers of film A, the total thickness of those layers can be the thickness of film A described above. When it has two or more layers of film B, the total thickness of those layers can be the thickness of film B described above.

[0022] In the prior art, no film that satisfies NZ(A)<0 and has a thickness ratio DB / DA that satisfies the above requirement is known, and in this respect the optical film of the present invention is novel. In the present invention, such an optical film is achieved by using a crystalline resin as the material for film A and adjusting the birefringence in the thickness direction by a specific manufacturing method described below.

[0023] The crystallinity of the crystalline polymer contained in film A is not particularly limited, but is usually high to a certain degree. The specific range of the crystallinity is preferably 10% or more, more preferably 15% or more, and particularly preferably 30% or more. The crystallinity of the crystalline polymer can be measured by X-ray diffraction.

[0024] [Materials that make up Film A] The crystalline resin (a) constituting the film A may be a resin containing a polymer having crystallinity. The "polymer having crystallinity" refers to a polymer having a melting point Tm. In other words, the "polymer having crystallinity" refers to a polymer whose melting point can be observed by a differential scanning calorimeter (DSC). In the following description, the polymer having crystallinity may be referred to as a "crystalline polymer". The crystalline resin is preferably a thermoplastic resin.

[0025] The crystalline polymer preferably has a positive inherent birefringence, so that the crystalline resin (a) has a positive inherent birefringence value. By using a crystalline resin having a positive inherent birefringence, it is particularly easy to manufacture an optical film that meets the requirements of the present invention, especially the requirement of NZ(A)<1.

[0026] The crystalline polymer may be, for example, polyester such as polyethylene terephthalate (PET) or polyethylene naphthalate (PEN); polyolefin such as polyethylene (PE) or polypropylene (PP); and is not particularly limited, but preferably contains an alicyclic structure. By using a crystalline polymer containing an alicyclic structure, the mechanical properties, heat resistance, transparency, low moisture absorption, dimensional stability and light weight of the retardation film can be improved. The polymer containing an alicyclic structure refers to a polymer having an alicyclic structure in the molecule. Such a polymer containing an alicyclic structure may be, for example, a polymer obtained by a polymerization reaction using a cyclic olefin as a monomer, or a hydrogenated product thereof.

[0027] Examples of the alicyclic structure include a cycloalkane structure and a cycloalkene structure. Among these, a cycloalkane structure is preferred because it is easy to obtain a retardation film having excellent properties such as thermal stability. The number of carbon atoms contained in one alicyclic structure is preferably 4 or more, more preferably 5 or more, and preferably 30 or less, more preferably 20 or less, and particularly preferably 15 or less. When the number of carbon atoms contained in one alicyclic structure is within the above range, mechanical strength, heat resistance, and moldability are highly balanced.

[0028] In the crystalline polymer containing an alicyclic structure, the ratio of the structural unit having an alicyclic structure to all structural units is preferably 30% by weight or more, more preferably 50% by weight or more, and particularly preferably 70% by weight or more. By increasing the ratio of the structural unit having an alicyclic structure as described above, heat resistance can be improved. The ratio of the structural unit having an alicyclic structure to all structural units can be 100% by weight or less. In addition, in the crystalline polymer containing an alicyclic structure, the remainder other than the structural unit having an alicyclic structure is not particularly limited and can be appropriately selected according to the purpose of use.

[0029] Examples of the crystalline polymer containing an alicyclic structure include the following polymer (α) to polymer (δ). Among these, polymer (β) is preferred because a retardation film having excellent heat resistance can be easily obtained. Polymer (α): A ring-opening polymer of a cyclic olefin monomer, which has crystallinity. Polymer (β): A hydrogenated product of polymer (α) and has crystallinity. Polymer (γ): An addition polymer of a cyclic olefin monomer, which has crystallinity. Polymer (δ): A hydrogenated polymer (γ) having crystallinity.

[0030] Specifically, the crystalline polymer containing an alicyclic structure is preferably a dicyclopentadiene ring-opening polymer having crystallinity, and a dicyclopentadiene ring-opening polymer hydrogenation product having crystallinity. Among them, a dicyclopentadiene ring-opening polymer hydrogenation product having crystallinity is particularly preferred. Here, the dicyclopentadiene ring-opening polymer refers to a polymer in which the ratio of dicyclopentadiene-derived structural units to all structural units is usually 50% by weight or more, preferably 70% by weight or more, more preferably 90% by weight or more, and even more preferably 100% by weight.

[0031] The hydrogenated ring-opening polymer of dicyclopentadiene preferably has a high ratio of racemo dyads. Specifically, the ratio of racemo dyads in the repeating units of the hydrogenated ring-opening polymer of dicyclopentadiene is preferably 51% or more, more preferably 70% or more, and particularly preferably 85% or more. A high ratio of racemo dyads indicates high syndiotactic stereoregularity. Therefore, the higher the ratio of racemo dyads, the higher the melting point of the hydrogenated ring-opening polymer of dicyclopentadiene tends to be. The ratio of racemo-dyads is described in the Examples below. 13 It can be determined based on C-NMR spectrum analysis.

[0032] As the polymer (α) to polymer (δ), polymers obtained by the production method disclosed in WO 2018 / 062067 can be used.

[0033] The melting point Tm of the crystalline polymer is preferably 200° C. or higher, more preferably 230° C. or higher, and preferably 290° C. or lower. By using a crystalline polymer having such a melting point Tm, an optical film having an even better balance between moldability and heat resistance can be obtained.

[0034] Generally, a crystalline polymer has a glass transition temperature, and therefore, the glass transition temperature can be observed for the crystalline resin (a) mainly composed of a crystalline polymer. The glass transition temperature Tg(a) of the crystalline resin (a) is not particularly limited, but is usually 85°C or higher and usually 170°C or lower.

[0035] The glass transition temperature Tg and melting point Tm of a polymer can be measured by the following method. First, the polymer is melted by heating, and the melted polymer is quenched with dry ice. Then, the glass transition temperature Tg and melting point Tm of the polymer can be measured by using this polymer as a test specimen with a differential scanning calorimeter (DSC) at a heating rate of 10°C / min (heating mode).

[0036] The weight average molecular weight (Mw) of the crystalline polymer is preferably 1,000 or more, more preferably 2,000 or more, and is preferably 1,000,000 or less, more preferably 500,000 or less. A crystalline polymer having such a weight average molecular weight has an excellent balance between moldability and heat resistance.

[0037] The molecular weight distribution (Mw / Mn) of the crystalline polymer is preferably 1.0 or more, more preferably 1.5 or more, and is preferably 4.0 or less, more preferably 3.5 or less. Here, Mn represents the number average molecular weight. A crystalline polymer having such a molecular weight distribution has excellent moldability.

[0038] The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the polymer can be measured in terms of polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as a developing solvent.

[0039] The crystalline polymer may be used alone or in combination of two or more kinds in any ratio.

[0040] The proportion of the crystalline polymer in the crystalline resin (a) is preferably 50% by weight or more, more preferably 70% by weight or more, and particularly preferably 90% by weight or more. When the proportion of the crystalline polymer is equal to or more than the lower limit, the birefringence development and heat resistance of the film A can be improved. The upper limit of the proportion of the crystalline polymer can be 100% by weight or less.

[0041] The crystalline resin (a) may contain optional components in addition to the crystalline polymer. Examples of the optional components include antioxidants such as phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants; light stabilizers such as hindered amine-based light stabilizers; waxes such as petroleum wax, Fischer-Tropsch wax, and polyalkylene wax; nucleating agents such as sorbitol-based compounds, metal salts of organic phosphoric acids, metal salts of organic carboxylic acids, kaolin, and talc; diaminostilbene derivatives, coumarin derivatives, and azole-based derivatives (e.g., benzoxazole derivatives, benzotriazole derivatives, and benzimide derivatives); and the like. Examples of the optional components include fluorescent brighteners such as benzothiazole derivatives, carbazole derivatives, pyridine derivatives, naphthalic acid derivatives, and imidazolone derivatives; ultraviolet absorbers such as benzophenone-based ultraviolet absorbers, salicylic acid-based ultraviolet absorbers, and benzotriazole-based ultraviolet absorbers; inorganic fillers such as talc, silica, calcium carbonate, and glass fibers; colorants; flame retardants; flame retardant assistants; antistatic agents; plasticizers; near-infrared absorbers; lubricants; fillers; and any polymer other than a crystalline polymer, such as a soft polymer. One type of optional component may be used alone, or two or more types may be used in combination at any ratio.

[0042] [Organic solvent contained in crystalline resin (a)] The crystalline resin (a) constituting the film A may contain a solvent such as an organic solvent. This solvent is usually incorporated into the film in step (III) of the production method of the present invention.

[0043] The whole or part of the solvent taken into the film in step (III) may penetrate into the inside of the polymer. Therefore, even if drying is performed at a temperature higher than the boiling point of the solvent, it is difficult to completely remove the solvent. Therefore, film A usually contains a solvent.

[0044] The solvent may be an organic solvent that does not dissolve the crystalline polymer. Preferable organic solvents include, for example, hydrocarbon solvents such as toluene, limonene, and decalin; and carbon disulfide. The type of organic solvent may be one type or two or more types.

[0045] The ratio of the organic solvent contained in the crystalline resin (a) (solvent content) relative to 100% by weight of the crystalline resin (a) is preferably 10% by weight or less, more preferably 5% by weight or less, and particularly preferably 0.1% by weight or less.

[0046] [Materials constituting protective film B] A preferred example of the material constituting the protective film B is the material (b) described below. As the material (b), a thermoplastic resin is usually used. The thermoplastic resin constituting the material (b) usually contains a polymer and may further contain any optional component as required. The polymer may usually be an amorphous polymer that does not have crystallinity.

[0047] Examples of polymers that can be included in the material (b) include polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyarylene sulfides such as polyphenylene sulfide; polyvinyl alcohol; polycarbonate; polyarylate; cellulose ester polymers, polyethersulfone; polysulfone; polyarylsulfone; polyvinyl chloride; polymers containing an alicyclic structure such as norbornene-based polymers; and rod-shaped liquid crystal polymers. The polymer may be used alone or in combination of two or more types in any ratio. The polymer may be a homopolymer or a copolymer. Among these, a polymer containing an alicyclic structure is preferred because it has excellent mechanical properties, heat resistance, transparency, low moisture absorption, dimensional stability, and light weight.

[0048] The alicyclic structure-containing polymer is a polymer whose structural unit contains an alicyclic structure. The alicyclic structure-containing polymer may have an alicyclic structure in the main chain or may have an alicyclic structure in the side chain. Among them, from the viewpoint of mechanical strength and heat resistance, the polymer containing an alicyclic structure in the main chain is preferred.

[0049] Examples of the alicyclic structure include saturated alicyclic hydrocarbon (cycloalkane) structures, unsaturated alicyclic hydrocarbon (cycloalkene, cycloalkyne) structures, etc. Among these, from the viewpoint of mechanical strength and heat resistance, cycloalkane structures and cycloalkene structures are preferred, and cycloalkane structures are particularly preferred.

[0050] The number of carbon atoms constituting the alicyclic structure is preferably 4 or more, more preferably 5 or more, and preferably 30 or less, more preferably 20 or less, and particularly preferably 15 or less, per one alicyclic structure. When the number of carbon atoms constituting the alicyclic structure is within the above range, the mechanical strength, heat resistance, and moldability of the resin containing the alicyclic structure-containing polymer are highly balanced.

[0051] The ratio of the structural unit having an alicyclic structure in the alicyclic structure-containing polymer may be appropriately selected depending on the purpose of use, and is preferably 55% by weight or more, more preferably 70% by weight or more, and particularly preferably 90% by weight or more. When the ratio of the structural unit having an alicyclic structure in the alicyclic structure-containing polymer is within this range, the transparency and heat resistance of the resin are good.

[0052] Examples of the alicyclic structure-containing polymer that can be included in the material (b) include norbornene-based polymers, monocyclic olefin polymers, cyclic conjugated diene polymers, vinyl alicyclic hydrocarbon polymers, and hydrogenated products thereof. Among these, norbornene-based polymers are preferred because of their good transparency and moldability.

[0053] Examples of norbornene-based polymers and their hydrogenated products include ring-opening polymers of monomers having a norbornene structure and their hydrogenated products; addition polymers of monomers having a norbornene structure and their hydrogenated products. Examples of ring-opening polymers of monomers having a norbornene structure include ring-opening homopolymers of one type of monomer having a norbornene structure, ring-opening copolymers of two or more types of monomers having a norbornene structure, and ring-opening copolymers of a monomer having a norbornene structure and any monomer that can be copolymerized therewith. Examples of addition polymers of monomers having a norbornene structure include addition homopolymers of one type of monomer having a norbornene structure, addition copolymers of two or more types of monomers having a norbornene structure, and addition copolymers of a monomer having a norbornene structure and any monomer that can be copolymerized therewith. Examples of these polymers include the polymers disclosed in JP-A-2002-321302 and the like. Among these, a hydrogenated product of a ring-opening polymer of a monomer having a norbornene structure is particularly suitable from the viewpoints of moldability, heat resistance, low moisture absorption, dimensional stability and light weight.

[0054] Specific examples of norbornene-based polymers and hydrogenated products thereof include "ZEONOR" manufactured by Zeon Corporation; "ARTON" manufactured by JSR Corporation; and "TOPAS" manufactured by TOPAS ADVANCED POLYMERS.

[0055] The weight average molecular weight (Mw) of the polymer that can be contained in the material (b) is preferably 10,000 or more, more preferably 15,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 80,000 or less, particularly preferably 50,000 or less. When the weight average molecular weight is within such a range, the mechanical strength and moldability of the protective film are highly balanced.

[0056] The molecular weight distribution (weight average molecular weight (Mw) / number average molecular weight (Mn)) of the polymer that can be contained in material (b) is preferably 1.2 or more, more preferably 1.5 or more, particularly preferably 1.8 or more, and is preferably 4.0 or less, more preferably 3.5 or less, particularly preferably 3.0 or less. When the molecular weight distribution is equal to or more than the lower limit of the above range, the productivity of the polymer can be increased and the production cost can be reduced. When the molecular weight distribution is equal to or less than the upper limit, the amount of low molecular weight components is reduced, thereby suppressing relaxation during exposure to high temperatures and improving the stability of the protective film.

[0057] The weight average molecular weight Mw and number average molecular weight Mn of the polymer can be measured in terms of polyisoprene by gel permeation chromatography (hereinafter abbreviated as "GPC") using cyclohexane as a solvent. If the polymer is not soluble in cyclohexane, they can be measured in terms of polystyrene by GPC using toluene as a solvent.

[0058] The amount of the polymer contained in the material (b) is preferably 50% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, even more preferably 80% by weight to 100% by weight, even more preferably 90% by weight to 100% by weight, and particularly preferably 95% by weight to 100% by weight, based on 100% by weight of the resin forming the resin film. When the amount of the polymer is within the above range, the properties of the polymer can be effectively exhibited.

[0059] The material (b) may contain any component other than the polymer. Examples of the optional components include additives such as colorants such as pigments and dyes, plasticizers, fluorescent whitening agents, dispersants, heat stabilizers, light stabilizers, ultraviolet absorbers, antistatic agents, antioxidants, fine particles, and surfactants. These components may be used alone or in combination of two or more at any ratio.

[0060] Usually, material (b) is a resin mainly composed of a polymer having a glass transition temperature, and therefore, the glass transition temperature of material (b) can also be observed. The glass transition temperature Tg(b) of material (b) is preferably 90°C or higher, more preferably 100°C or higher, particularly preferably 110°C or higher, and preferably 200°C or lower, more preferably 190°C or lower, particularly preferably 180°C or lower. When the glass transition temperature Tg(b) of material (b) is the lower limit or higher, the durability of protective film B in a high-temperature environment can be improved. In addition, when the glass transition temperature Tg(b) of material (b) is the upper limit or lower, the stretching process of the multilayer film including protective film B can be smoothly performed.

[0061] The glass transition temperature Tg(b) of the material (b) is preferably relatively higher than the glass transition temperature Tg(a) of the crystalline resin (a). Specifically, it is preferable that Tg(b)≧Tg(a), it is preferable that Tg(b)≧Tg(a)+30(℃), and it is more preferable that Tg(b)≧Tg(a)+35(℃). By having the ratio of Tg(a) and Tg(b) within the above range, the co-stretching can be performed in a state where the crystalline resin (a) is well supported by the material (b), and as a result, the optical film of the present invention having the desired optical properties can be easily produced.

[0062] [Any layer] The optical film of the present invention may consist of only film A and protective film B, but may further include any layer(s) in addition to these. For example, it may include an adhesive layer that is interposed between film A and protective film B and bonds them together with an appropriate adhesive strength.

[0063] [Method for producing optical film] The optical film of the present invention can be produced by a production method including the following steps (I) to (III). Such a production method will be described below as a method for producing the optical film of the present invention. The method for producing the optical film of the present invention can further include the following step (IV) in addition to the steps (I) to (III). Step (I): A film pA made of a crystalline resin (a) is prepared. Step (II): A protective film B is laminated to one surface of the film pA. Step (III): The other surface of the film pA is brought into contact with a solvent to change the birefringence in the thickness direction of the film pA to form film A. Step (IV): After step (III), film A and protective film B are co-stretched.

[0064] In the explanation of this application, film A and protective film B which have been subjected to step (III) and before being subjected to step (IV), and film A and protective film B which have been subjected to step (IV), may be referred to by the same name; however, in the following explanation, when it is necessary to distinguish between them for the sake of convenience, the former will be referred to as film qA and protective film qB, and the latter will be referred to as film rA and protective film rB.

[0065] In the following, the film obtained as a result of step (II) and having film pA and protective film B may be referred to as multilayer film (II). Similarly, among the optical films of the present invention, the optical film obtained as a result of step (III) may be referred to as optical film (III), and the optical film obtained as a result of carrying out step (III) and step (IV) may be referred to as optical film (IV).

[0066] [Process (I)] Step (I) can be carried out by any process capable of forming the crystalline resin (a) into a film shape. Molding by melt extrusion molding is preferred from the viewpoint of efficiently producing a long film pA. Specifically, a long film pA of the crystalline resin (a) can be formed by melt extrusion molding the crystalline resin (a) in an extrusion device equipped with a die for normal extrusion molding. The molding conditions can be appropriately adjusted according to the properties of the crystalline resin (a). The thickness of the film pA prepared in step (I) is not particularly limited, and can be appropriately adjusted so that the thickness of the film A (film qA or film rA) in the optical film as a product has a desired value. The film pA may be a film having optical anisotropy, but even if it does not have optical anisotropy, the optical film of the present invention can be easily produced by subjecting it to the subsequent process.

[0067] [Step (II)] The step (II) can be carried out by preparing a protective film B separately from the film pA and laminating them together. By this lamination operation, a multilayer film (II) including the film pA and the protective film is obtained.

[0068] The protective film B to be subjected to the step (II) may be a film of the material (b) described above. A commercially available film may be used as the protective film B to be subjected to the step (II). In addition, a multilayer film (II) having a layer structure of (film pA) / (adhesive layer) / (protective film B) may be obtained by preparing a multilayer film having a multilayer structure including the protective film B and an adhesive layer and laminating the multilayer film with the film pA.

[0069] [Step (III)] In step (III), a solvent is brought into contact with the surface of the film pA opposite to the surface to which the protective film B is attached. As the solvent, a solvent capable of penetrating into the crystalline resin (a) without dissolving the resin can be appropriately selected. As the solvent, an organic solvent is usually used. Examples of the organic solvent include hydrocarbon solvents such as toluene, limonene, and decalin; and carbon disulfide. The type of solvent may be one type or two or more types.

[0070] The contact in step (III) can be achieved by any operation. Examples of the contact operation include a spray method in which a solvent is sprayed on the surface of the film pA side of the multilayer film (II); a coating method in which a solvent is applied to the surface of the film pA side; and an immersion method in which the multilayer film (II) is immersed in a solvent. From the viewpoint of easily achieving continuous contact, the immersion method is preferred. However, when the protective film B is a material that is easily dissolved by contact with a solvent, an operation that can achieve contact of the solvent with only one side of the film (II) is preferred, and such an operation is an operation other than the immersion method, and specifically, it can be a spray method or a coating method.

[0071] The temperature of the solvent during the contact in step (III) may be any temperature within a range in which the solvent can maintain a liquid state, and therefore may be set within a range from the melting point to the boiling point of the solvent.

[0072] When the multilayer film (II) is contacted with the solvent by immersion, the contact time is preferably 0.5 seconds or more, more preferably 1.0 second or more, and particularly preferably 5.0 seconds or more, and is preferably 120 seconds or less, more preferably 80 seconds or less, and particularly preferably 60 seconds or less. When the multilayer film (II) and the solvent are brought into contact with each other by coating the solvent, the coating thickness calculated from the coating area and the amount of the solvent supplied can be appropriately adjusted. The coating thickness is preferably 5 μm or more, more preferably 10 μm or more, and is preferably 100 μm or less. When the contact time or coating thickness is equal to or greater than the lower limit, the NZ coefficient of film A can be effectively adjusted by contact with the solvent. On the other hand, even if the contact time is longer than the upper limit or the coating thickness is thicker than the upper limit, the adjustment amount of the NZ coefficient tends not to change significantly. Therefore, when the contact time or coating thickness is equal to or less than the upper limit, the productivity can be increased without impairing the quality of film A.

[0073] The multilayer film obtained through step (III) may be used as the optical film (III) of the present invention as it is. Alternatively, the multilayer film obtained through step (III) may be further subjected to an arbitrary step and then used as the optical film (III) of the present invention. For example, the film obtained through step (III) may be heated while maintaining its dimensions to perform a step of increasing the crystallinity.

[0074] As a result of the contact with the solvent in step (III), the refractive index of film pA changes to become film qA, and an optical film (III) including film qA and protective film qB is obtained. When changing from film pA to film qA, the thickness may increase along with such a change in refractive index. Such a change brought about by the contact with the solvent is difficult to obtain by a conventional method for manufacturing a retardation film, such as simply stretching the resin for the optical film. Therefore, as a result of such a change, it becomes possible to easily manufacture the optical film of the present invention.

[0075] Film qA in the optical film (III) may have an NZ coefficient NZ(qA) of less than 1, specifically, it may satisfy NZ(qA) < 0. Therefore, film qA in the optical film (III) can be easily converted into a film satisfying 0 < NZ(A) < 1 by a simple treatment such as uniaxial stretching in step (IV). NZ(qA) is preferably 0.7 or less, more preferably 0.6 or less. The lower limit of NZ(A) is not particularly limited, but may be 0.3 or more.

[0076] 〔Step (IV)〕 In step (IV), after step (III), the film qA and the protective film qB are co-stretched. Specifically, the optical film (III) obtained in step (III) is stretched to co-stretch the film qA and the protective film qB. By such co-stretching, all layers included in the optical film (III) are stretched at the same stretching ratio and in the same stretching direction, and the polymer molecules included in these layers are oriented in a direction according to the stretching direction. Since the optical film (III) has been subjected to step (III), as a result of step (IV), an optical film (IV) having optical properties that are difficult to obtain by a normal retardation film manufacturing method such as simply stretching a resin for an optical film can be easily obtained.

[0077] The stretching in the step (IV) may be uniaxial stretching or biaxial or more stretching. The number of times of stretching may be one or more than one. One uniaxial stretching is preferable. Since the optical film (III) has been subjected to the step (III), such a one-time uniaxial stretching can easily produce an optical film (IV) having optical properties that are difficult to obtain by a normal retardation film manufacturing method.

[0078] The stretching direction in step (IV) is not limited, and examples thereof include the longitudinal direction, the width direction, the oblique direction, etc. Here, the oblique direction refers to a direction perpendicular to the thickness direction and forming an angle of neither 0° nor 90° with the width direction (i.e., a direction forming an angle of more than 0° and less than 90° with the width direction).

[0079] When a film having optical properties equivalent to the optical film (IV) of the present invention is produced by a production method not including step (III), multiple complicated stretching steps are usually required. When optical properties are expressed by stretching, the stretching conditions must be strictly controlled, so the number of stretching steps is a major disadvantage in terms of production efficiency. In contrast, the production method of the present invention is advantageous in terms of production efficiency because the optical film (IV) of the present invention can be obtained by only uniaxial stretching.

[0080] The stretching ratio is preferably 1.1 times or more, more preferably 1.2 times or more, and is preferably 20.0 times or less, more preferably 10.0 times or less, even more preferably 5.0 times or less, and particularly preferably 2.0 times or less. It is desirable to appropriately set the specific stretching ratio according to factors such as the optical properties, thickness, and strength of the optical film (IV) to be the product. When the stretching ratio is equal to or more than the lower limit, the birefringence can be significantly changed by stretching. On the other hand, when the stretching ratio is equal to or less than the upper limit, the direction of the slow axis can be easily controlled and breakage of the film can be effectively suppressed.

[0081] The stretching temperature can be specified relative to the glass transition temperature Tg(a) of the crystalline resin (a). The stretching temperature is preferably "Tg(a)+5"°C or higher, more preferably "Tg(a)+10"°C or higher, and preferably "Tg(a)+100"°C or lower, more preferably "Tg(a)+90"°C or lower. When the stretching temperature is equal to or higher than the lower limit, the film can be sufficiently softened to perform uniform stretching. When the stretching temperature is equal to or lower than the upper limit, the film can be prevented from hardening due to the progress of crystallization of the crystalline polymer, so that the stretching can be performed smoothly, and a large birefringence can be developed by stretching. Furthermore, the haze of the optical film (IV) obtained can usually be reduced to increase the transparency. In addition, by performing stretching at such a temperature, the crystallinity of the crystalline resin (a) is increased, and the optical properties of the film A of the optical film (IV) obtained as a result can be easily adjusted to a desired range.

[0082] Since the birefringence can be changed by the step (IV), the NZ coefficient can be adjusted. Thus, the optical film (IV) having the desired optical properties can be obtained by the stretching in the step (IV). The film obtained as a result of the step (IV) can be used as it is as the optical film (IV) of the present invention. Alternatively, the obtained film can be further subjected to any processing to become the optical film (IV) of the present invention. Examples of the optional processing include adjustment of the birefringence by heat treatment while maintaining the stretched dimension or relaxation treatment by reducing the stretched dimension.

[0083] In the optical film (IV), the film rA has an NZ coefficient NZ(rA) of less than 1. Specifically, it can satisfy 0 < NZ(A) < 1. Such a film can be usefully used as a so-called three-dimensional retardation film. NZ(rA) is preferably 0.2 or more, and on the other hand, preferably 0.8 or less. When the optical film is provided in a display device such as a liquid crystal display device, the effect of reducing the coloring of the display surface viewed from the tilt direction can be particularly well exhibited when NZ(rA) is within this range.

[0084] [Other steps] The method for manufacturing the optical film of the present invention may further include an arbitrary step in combination with the steps described above. For example, after step (III), it may include a step of removing the solvent attached to the film. Examples of the method for removing the solvent include drying, wiping, etc.

[0085] The long optical film (III) obtained by step (III) and the long optical film (IV) obtained by step (IV) can be wound into a roll as a film roll if necessary.

[0086] [Method for manufacturing a retardation film] The optical films of the present invention (optical film (III) and optical film (IV)) can be used as they are for optical applications, but further, they can be subjected to a step of peeling the protective film B from the optical film, and only the remaining film A can be used as a retardation film.

[0087] [Applications] The optical film of the present invention and the retardation film of the present invention can be used as components of an optical device such as a display device after being processed into a desired shape such as a rectangle if necessary. When the optical film of the present invention or the retardation film of the present invention is used as a component of a display device, the display quality such as the viewing angle, contrast, and image quality of the image displayed on the display device can be improved.

Examples

[0088] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the examples shown below, and can be modified and carried out as desired without departing from the scope of the claims of the present invention and the scope of equivalents thereto. In the following description, the units "%" and "parts" are by weight unless otherwise specified. Furthermore, the operations described below were carried out at room temperature and pressure unless otherwise specified.

[0089] (Method of measuring weight average molecular weight Mw and number average molecular weight Mn of polymer) The weight average molecular weight Mw and number average molecular weight Mn of the polymer were measured as polystyrene equivalent values ​​using a gel permeation chromatography (GPC) system (Tosoh Corporation, "HLC-8320"). In the measurement, an H-type column (Tosoh Corporation) was used as the column, and tetrahydrofuran was used as the solvent. The temperature during the measurement was 40°C.

[0090] (Method of measuring hydrogenation rate of polymer) The hydrogenation rate of the polymer is 4 as a solvent at 145°C, 1 Measured by H-NMR measurement.

[0091] (Method of measuring glass transition temperature Tg and melting point Tm) The glass transition temperature Tg and melting point Tm of the polymer were measured as follows. First, the polymer was melted by heating, and the melted polymer was quenched with dry ice. Then, the glass transition temperature Tg and melting point Tm of the polymer were measured using a differential scanning calorimeter (DSC) at a heating rate of 10°C / min (heating mode) using the polymer as a test specimen.

[0092] (Method for measuring the ratio of racemo-dyads in polymers) The ratio of racemo-dyads in the polymer was determined as follows. 4The inverse-gated decoupling method was applied to the polymer at 200°C using 13 C-NMR measurements were performed. 13 The results of C-NMR measurement showed that o-dichlorobenzene-d 4 Using the peak at 127.5 ppm as the reference shift, the signal at 43.35 ppm from the meso-dyad and the signal at 43.43 ppm from the racemo-dyad were identified. The ratio of the racemo-dyads in the polymer was calculated based on the intensity ratio of these signals.

[0093] (Method of measuring optical properties of film) The in-plane retardation Re, thickness retardation Rth and NZ coefficient of the optical film were measured at a wavelength of 590 nm using a birefringence meter (Axometrics' "AxoScan") The measurements were performed at multiple points at 5 cm intervals in the width direction of the film, and the average value of the measurements at each point was used as the measurement result.

[0094] (Method of measuring film thickness) The thickness was measured at multiple points at 5 cm intervals across the width of the film using a snap gauge (Mitutoyo ID-C112BS). The average thickness of the film was calculated by averaging the measured values.

[0095] (Crystallization degree) The crystallinity (%) of the crystalline polymer was measured by X-ray diffraction method.

[0096] (Curl evaluation) A piece of film was cut from the center of the width direction of the long film to be evaluated to obtain a rectangular sample of 100 mm length x 100 mm width. The sample was placed on a flat stage and left at 23°C for 1 hour. After that, the height of each of the four corners of the sample raised above the stage was measured with a ruler. The average value of the measurement results at the four points was regarded as the amount of curl of the film. The amount of curl was evaluated according to the following criteria. Good: The curl amount is less than 4 mm. Poor: The curl amount is 4 mm or more.

[0097] (Winding deformation evaluation) Immediately after obtaining the film roll of the long film to be measured, the deformation state of the winding of the film roll was evaluated according to the following criteria. 5: No deformation of the winding 4: Almost no deformation of the winding 3: The winding is slightly deformed. 2: The deformation of the roll is clearly visible. 1: Large deformation of the winding For practical purposes, a rating of 4 or higher is considered to be a usable level.

[0098] (Evaluation of deterioration over time within the roll) The film roll of the long film to be measured was stored in a high temperature (38°C) and high humidity (75%) atmosphere for about 2 weeks, and then the film was unwound from the film roll and the protective film was peeled off in the middle of the roll (i.e., at the middle part in the longitudinal direction of the film) to obtain a retardation film consisting of only film A. A rectangular area of ​​100 cm x 100 cm of the obtained retardation film was visually observed for the presence or absence of folds and wrinkles with a diameter of 1 mm or more, and evaluated according to the following criteria. ○: No folds or wrinkles. △: The total number of folds and wrinkles is less than 5. ×: The total number of folds and wrinkles is 5 or more.

[0099] [Production Example 1: Hydrogenation product of ring-opening polymer of dicyclopentadiene] A metallic pressure reactor was thoroughly dried and then purged with nitrogen. 154.5 parts of cyclohexane, 42.8 parts of a 70% cyclohexane solution of dicyclopentadiene (endo isomer content of 99% or more) (30 parts as dicyclopentadiene), and 1.8 parts of 1-hexene were added to the metallic pressure reactor and heated to 53°C.

[0100] A solution was prepared by dissolving 0.014 parts of tetrachlorotungsten phenylimide (tetrahydrofuran) complex in 0.70 parts of toluene. 0.061 parts of a 19% diethylaluminum ethoxide / n-hexane solution was added to the solution and stirred for 10 minutes to prepare a catalyst solution. The catalyst solution was added to the mixture in the pressure-resistant reactor to initiate the ring-opening polymerization reaction. The reaction was then continued for 4 hours while maintaining the temperature at 53°C, yielding a solution of ring-opened polymer of dicyclopentadiene. The number average molecular weight (Mn) and weight average molecular weight (Mw) of the obtained ring-opened polymer of dicyclopentadiene were 8,830 and 29,800, respectively, and the molecular weight distribution (Mw / Mn) calculated from these was 3.37.

[0101] To 200 parts of the obtained solution of the ring-opening polymer of dicyclopentadiene, 0.037 parts of 1,2-ethanediol was added as a terminator, heated to 60°C, and stirred for 1 hour to terminate the polymerization reaction. One part of a hydrotalcite-like compound (Kyowa Chemical Industry Co., Ltd.'s "Kyoward (registered trademark) 2000") was added, heated to 60°C, and stirred for 1 hour. Thereafter, 0.4 parts of a filter aid (Showa Chemical Industry Co., Ltd.'s "Radiolight (registered trademark) #1500") was added, and the adsorbent and the solution were filtered using a PP pleated cartridge filter (ADVANTEC Toyo Co., Ltd.'s "TCP-HX").

[0102] 100 parts of cyclohexane was added to 200 parts of the solution of the ring-opened polymer of dicyclopentadiene after filtration (polymer amount: 30 parts), and 0.0043 parts of chlorohydridocarbonyltris(triphenylphosphine)ruthenium was added, and the hydrogenation reaction was carried out at a hydrogen pressure of 6 MPa and 180°C for 4 hours. As a result, a reaction liquid containing a hydrogenated product of the ring-opened polymer of dicyclopentadiene was obtained. The reaction liquid was a slurry solution in which the hydrogenated product had precipitated.

[0103] The hydrogenated product and the solution contained in the reaction solution were separated using a centrifuge and dried under reduced pressure at 60°C for 24 hours to obtain 28.5 parts of a hydrogenated product of a crystalline ring-opening polymer of dicyclopentadiene. The hydrogenation rate of this hydrogenated product was 99% or more, the glass transition temperature Tg was 97°C, the melting point Tm was 266°C, and the ratio of racemo-dyads was 89%.

[0104] [Production Example 2: Pellets of crystalline resin (a)] Crystalline resin (a) was obtained by mixing 100 parts of the hydrogenated product of the ring-opening polymer of dicyclopentadiene obtained in Production Example 1 with 0.5 parts of an antioxidant (tetrakis[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane; "Irganox (registered trademark) 1010" manufactured by BASF Japan Ltd.).

[0105] The obtained crystalline resin (a) was put into a twin-screw extruder (Toshiba Machine Co., Ltd., "TEM-37B") equipped with four die holes with an inner diameter of 3 mm. The resin was subjected to hot melt extrusion molding using the twin-screw extruder to form a strand-shaped molded body. This molded body was chopped with a strand cutter to obtain pellets of the crystalline resin (a).

[0106] Example 1 (1-1. Step (I): Film pA) The pellets of crystalline resin (a) obtained in Production Example 2 were fed to a hot melt extrusion film molding machine equipped with a T-die. Using this film molding machine, the crystalline resin (a) was formed into a film under the following operating conditions, and taken up on a roll at a speed of 27 m / min. Barrel temperature setting: 280℃~290℃ Die temperature: 270℃ Screw speed: 145 rpm Cast roll temperature: 70℃ As a result, a long film pA made of the crystalline resin (a) was obtained. The obtained film pA had a width of 120 mm and a thickness of 68 μm.

[0107] The in-plane retardation Re(pA) of film pA at a wavelength of 590 nm was 5 nm, the thickness direction retardation Rth(pA) was 5 nm, and the slow axis direction was the width direction relative to the longitudinal direction.

[0108] (1-2. Step (II): Attachment of protective film B) A protective film with an adhesive layer (a film having protective film B and an adhesive layer) was prepared. Protective film B in the protective film with an adhesive layer (product name "ZEONORFILM ZF14-188", manufactured by Zeon Corporation) was a film made of a material (b) (glass transition temperature 137°C) containing an alicyclic structure-containing polymer with a thickness of 188 μm. Protective film B had an in-plane retardation of 10 nm and a thickness retardation of 15 nm at a wavelength of 590 nm.

[0109] A protective film with an adhesive layer was attached to one surface of the film pA obtained in (1-1) with the adhesive layer facing in the direction of contact. This resulted in a multilayer film (II) having a layer structure of (film pA) / (adhesive layer) / (protective film B). The ratio of (protective film B thickness) / (film pA thickness) was 2.76.

[0110] (1-3. Step (III): Solvent Contact) The multilayer film (II) obtained in (1-2) was continuously transported along the longitudinal direction, and toluene was applied to the surface of the film pA in the multilayer film (II) opposite to the protective film B using a die coater. This operation changed the birefringence in the thickness direction of the film pA to film qA, and an optical film (III) having a layer structure of (film qA) / (adhesive layer) / (protective film B) was obtained. The optical film (III) was wound around a core to form a film roll.

[0111] (1-4. Process (IV): Co-stretching) The optical film (III) obtained in (1-3) was unwound from the film roll and stretched using a stretching machine. This stretching machine has a structure equipped with a plurality of clips capable of gripping both ends of the film, and the film can be stretched by moving the clips. The stretching temperature was 145°C, the stretching direction was the film width direction, and the stretching ratio was 1.15 times, and fixed-end uniaxial stretching was performed. By this operation, the optical film (III) was stretched, the optical anisotropy of the film qA was changed to film rA, and an optical film (IV) having a layer structure of (film rA) / (adhesive layer) / (protective film B) was obtained. The optical film (IV) was wound around a core to form a film roll. The total length of the obtained film was 1000 m.

[0112] (1-5. Rating) In the optical film (IV) obtained in (1-4), the thickness of film rA was 70 μm, and the thickness of protective film B was 164 μm. Therefore, the ratio of (thickness of protective film B) / (thickness of film rA) was 2.34. The in-plane retardation Re(rA) of film rA at a wavelength of 590 nm was 125 nm, the thickness direction retardation Rth(rA) was -7 nm, the NZ coefficient was 0.44, and the slow axis direction was perpendicular to the longitudinal direction. The crystallinity of film rA was measured to be 25%.

[0113] The optical film (IV) and the film roll thereof were evaluated for curl, deformation during rolling, and deterioration over time during rolling.

[0114] Example 2 Except for the fact that the stretching ratio of the co-stretching in (1-4) was 1.00 times, the same operation as in Example 1 was carried out and evaluation was performed. That is, in the step (1-4), stretching was not performed, and the film was moved and heated in a stretching machine at a temperature of 145° C. while maintaining the film dimensions, and an optical film was produced and evaluated.

[0115] Comparative Example 1 The protective film B of (1-2) was not attached. That is, in (1-3), the film pA obtained in (1-1) was used as it was instead of the multilayer film (II) obtained in (1-2), and the evaluation was performed in the same manner as in Example 1.

[0116] Comparative Example 2 In (1-2), a protective film B different from that used in (1-2) (product name "ZEONORFILM ZF14-040", manufactured by Zeon Corporation, made of the same material as that used in (1-2), thickness 40 μm) was used, and the evaluation was carried out in the same manner as in Example 1.

[0117] The outline of the operations and the evaluation results of the examples and comparative examples are shown in Table 1.

[0118] [Table 1]

[0119] As is clear from the results of the Examples and Comparative Examples, the optical film of the present invention obtained by the manufacturing method of the present invention can be a film that has a film A with an NZ coefficient of less than 1, while suppressing the occurrence of curling, deformation of the wound shape of the film roll, and film deterioration.

Claims

1. A long optical film comprising a film A made of a crystalline resin (a) and a protective film B provided on one surface of the film A, The thickness DA of the film A and the thickness DB of the protective film B satisfy DB / DA>2, The NZ coefficient of the film A is less than 1; The protective film B is made of material (b), An optical film, wherein the glass transition temperature Tg(a) (°C) of the crystalline resin (a) and the glass transition temperature Tg(b) (°C) of the material (b) satisfy Tg(b) ≧ Tg(a) + 35.

2. The optical film according to claim 1 , wherein the crystalline resin (a) has a positive intrinsic birefringence value.

3. The optical film according to claim 1 , wherein the crystalline resin (a) comprises an alicyclic structure-containing polymer.

4. A method for producing the optical film according to any one of claims 1 to 3, comprising the steps of: A step (I) of preparing a film pA made of a crystalline resin (a); A step (II) of laminating a protective film B onto one surface of the film pA; and (III) a step of contacting the other surface of the film pA with a solvent to change the birefringence in the thickness direction of the film pA to form the film A.

5. The method for producing an optical film according to claim 4 , further comprising, after the step (III), a step (IV) of co-stretching the film A and the protective film B.

6. A step of producing the optical film by the production method according to claim 4 or 5; and A method for producing a retardation film, comprising: a step (V) of peeling off the protective film B from the optical film.

Citation Information

Patent Citations

  • Method for producing retardation film

    JP2008281667A

  • Molded product of cycloolefin polymer and method for producing the same

    JP2009120755A

  • Optical laminate and liquid crystal display device

    JP2015031753A

  • Method for producing resin film, resin film, and optical film

    JP2016026909A

  • Optical laminate, polarizing plate and liquid crystal display device

    WO2016147764A1